Construction of Eukaryotic Cell Biomimetics: Hierarchical Polymersomes‐in‐Proteinosome Multicompartment with Enzymatic Reactions Modulated Protein Transportation. Issue 7 (29th December 2020) - Wen, Ping; Wang, Xueyi; Moreno, Silvia; Boye, Susanne; Voigt, Dagmar; Voit, Brigitte; Huang, Xin; Appelhans, Dietmar
Abstract: The eukaryotic cell is a smart compartment containing an outer permeable membrane, a cytoskeleton, and functional organelles, presenting part structures for life. The integration of membrane‐containing artificial organelles (=polymersomes) into a large microcompartment is a key step towards the establishment of exquisite cellular biomimetics with different membrane properties. Herein, an efficient way to construct a hierarchical multicompartment composed of a hydrogel‐filled proteinosome hybrid structure with an outer homogeneous membrane, a smart cytoskeleton‐like scaffold, and polymersomes is designed. Specially, this hybrid structure creates a micro‐environment for pH‐responsive polymersomes to execute a desired substance transport upon response to biological stimuli. Within the dynamic pH‐stable skeleton of the protein hydrogels, polymersomes with loaded PEGylated insulin biomacromolecules demonstrate a pH‐responsive reversible swelling‐deswelling and a desirable, on‐demand cargo release which is induced by the enzymatic oxidation of glucose to gluconic acid. This stimulus responsive behavior is realized by tunable on/off states through protonation of the polymersomes membrane under the enzymatic reaction of glucose oxidase, integrated in the skeleton of protein hydrogels. The integration of polymersomes‐based hybrid structure into the proteinosome compartment and the stimuli‐response on enzyme reactions fulfills the requirements of eukaryotic cell biomimetics in complex architectures and allows mimicking cellular transportation processes. Abstract : Eukaryotic cell biomimetics are realized by the construction of cell‐like multicompartmental micro‐sized structures (CMMS) containing proteinosome hybrid structures with smart cytoskeleton‐like hydrogel scaffold, pH‐responsive artificial organelles, and orthogonal‐responsive membranes. Under the stimuli of enzymatic reactions producing acid within CMMS, thus bio(macro)molecules transport and controlled release processes can be carried out for mimicking pancreatic ß‐cells.